2021
DOI: 10.48550/arxiv.2112.09985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalable Bicriteria Algorithms for Non-Monotone Submodular Cover

Abstract: This paper proposes the optimization problem Non-Monotone Submodular Cover (SC), which is to minimize the cost required to ensure that a non-monotone submodular benefit function exceeds a given threshold. Two algorithms are presented for SC that both give a ((1 + )(4/ 2 + 1), 1/2(1 − )) bicriteria approximation guarantee to the problem. Both algorithms process the ground set in a stream, one in multiple passes. Further, a (1/2(1 − ), (1 + )(4/ 2 + 1)) bicriteria approximation guarantee is given for the related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As statement in the introduction, Feige et al [18] showed that there is a close collection between the problems of submodular maximization and submodular cover. Based on the previous work, especially Crawford [19] , we know the following theorem still holds. We refer the reader to the detailed proof in the work of Crawford [19] .…”
Section: Streaming Algorithms For Approximately Submodular Cover Problemmentioning
confidence: 95%
See 2 more Smart Citations
“…As statement in the introduction, Feige et al [18] showed that there is a close collection between the problems of submodular maximization and submodular cover. Based on the previous work, especially Crawford [19] , we know the following theorem still holds. We refer the reader to the detailed proof in the work of Crawford [19] .…”
Section: Streaming Algorithms For Approximately Submodular Cover Problemmentioning
confidence: 95%
“…Based on the previous work, especially Crawford [19] , we know the following theorem still holds. We refer the reader to the detailed proof in the work of Crawford [19] .…”
Section: Streaming Algorithms For Approximately Submodular Cover Problemmentioning
confidence: 95%
See 1 more Smart Citation